A Diffuse Analysis Based on Analytical Processes to Prioritize Barriers in the Development of Renewable Energy Technologies in Alignment with the United Nations Sustainable Development Goals: Evidence from Guajira/Colombia - Moreno Rocha, Christian Manuel; Pertuz Ortiz, Jorge D.; Rodriguez Ibanez, Neyder A. (International Journal of Energy Economics and Policy, 2023)
Colombia is a country that is characterized by having potential in many renewable and sustainable energy sources such as solar, wind, hydroelectric, biomass, etc., in this country the growth value of renewable energy (ER) has not yet reached a benchmark, this due to the existence of several barriers or limitations that have hindered the path of research and implementation. It is difficult to identify and prioritize the impact of these barriers that mostly hinder growth or improvement in the quality of life of a specific population. For this research, a systematic structure has been developed to identify and prioritize the barriers and manage to find a solution path to the aforementioned. This study aims to recognize and classify the barriers according to their impact on the development of renewable energy technologies, as well as demonstrate the non-relationship that may exist between a territory rich in energy potential and the good quality of life of its inhabitants, the study consists of four phases; (1) A study area was taken for its characterization in renewable energy potential and compared with the current quality of its inhabitants, (2) The barriers were recognized from the available literature studies, project reports and interactions with 6 experts from academia and industries, (3) for the final selection, the FAHP decision method was used, then, 24 were selected and classified into five groups: social and economic barriers, political and, administrative and market barriers and geographical and environmental barriers and (4) the FAHP method was used to obtain the priority weight and the hierarchy between these barriers. The results showed first that there is no relationship indicating that a potential area in renewable energy source has a positive impact on people’s quality of life, also that politics and political barriers occupies the first place among the main barriers, besides that corruption and nepotism is the most relevant sub-criterion according to the experts’ results. Sensitivity analysis is used to confirm the stability of all prioritized barriers.